TRANSLATING DEVELOPMENT AID INTO CITY MANAGEMENT: THE BARRIO ACAHUALINCA INTEGRATED DEVELOPMENT PROGRAMME IN MANAGUA, NICARAGUA. (28th June 2012) - Zapata Campos, María José; Zapata, Patrik
SUMMARY This article seeks to understand how development aid is translated into city management practice in the global South and the implications of this for the power dynamics between municipal governments and international aid agencies. The study examines La Chureca, the rubbish dump and slum of Managua, Nicaragua, and its regeneration programme, the Barrio Acahualinca Integrated Development Programme. In the article, we explore the formulation and initial implementation of the Programme in terms of the construction of an action net in which, by a chain of translations, the Programme was transformed from an aid programme managed by international aid organisations into the management practice of the city of Managua. Despite the silent infiltration of important issues brought to the municipal political agenda by the development aid programme, small acts of defiance and resistance were also enacted by local actors who twisted the Programme to fit local needs. Copyright © 2012 John Wiley & Sons, Ltd.